Culture, stress and employee engagement in mergers and acquisitions - Bartling, Erin E. (University of Wisconsin--Stout, 2018)
Mergers and acquisitions are strategic purchases made by companies that routinely fail to meet their financial expectations. Organizational culture is a key part to merger and acquisition success and companies must have strategies to integrate these acquired companies into their culture. In addition to cultural integration, employees face stress throughout the integration process due to new leadership, new co-workers and new ways of getting work done in the organization. This stress can cause decreased organizational commitment and decreased employee engagement. When employees are not engaged they are not contributing positively to overall company goals. Strong communication and an associate's relationship with their coworkers and manager are critical in minimizing employee stress in a merger and acquisition. Company XYZ utilized an employee engagement survey in their acquisition integration process in 2017, as a way to understand how employees are engaging in the cultural beliefs, reacting to the change that comes from the integration process, and maintaining organizational commitment and employee engagement. The results from these surveys indicated that employees were engaged in the cultural beliefs of Company XYZ and understood the change that came as a result of the integration process. However, organizational commitment and employee engagement declined throughout the integration process.
Keywords: Consolidation and merger of corporations; Corporate culture; Employees